2017
DOI: 10.1111/jth.13583
|View full text |Cite
|
Sign up to set email alerts
|

Association between small‐intestinal bacterial overgrowth and deep vein thrombosis in patients with spinal cord injuries

Abstract: To cite this article: Cheng X, Zhang L, Xie N-C, Xu H-L, Lian Y-J. Association between small-intestinal bacterial overgrowth and deep vein thrombosis in patients with spinal cord injuries. J Thromb Haemost 2017; 15: 304-11. Essentials• Gastrointestinal dysfunction and vein thrombosis are complications after spinal cord injuries (SCI).• We assess the deep vein thrombosis (DVT) and small intestinal bacterial overgrowth (SIBO) in SCI.• 76 of the 377 SCI patients were DVT positive (20.2%) and 145 were defined as S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…Further, the reported incidence rate of DVT varied, ranged from 10% to 30% [23]. A previous study in Chinese patients with DVT found that 20.2% patients experienced DVT in the following 3-month after SCI [24]. Consistent with those results, our study showed that 18.8% of the SCI patients were determined as DVT in the follow-up of 1-month.…”
Section: Discussionsupporting
confidence: 87%
“…Further, the reported incidence rate of DVT varied, ranged from 10% to 30% [23]. A previous study in Chinese patients with DVT found that 20.2% patients experienced DVT in the following 3-month after SCI [24]. Consistent with those results, our study showed that 18.8% of the SCI patients were determined as DVT in the follow-up of 1-month.…”
Section: Discussionsupporting
confidence: 87%
“…Although gastrointestinal symptoms are frequently observed in patients with SCI, there are few reports of SIBO in SCI patients. Cheng et al report that 39% (145 of 377) of SCI patients were diagnosed with SIBO based on the glucose hydrogen/methane breath test [ 22 ]. However, the prevalence of SIBO among SCI patients as confirmed by the consensus diagnostic criteria of the presence of more than 10 5 CFU/mL bacteria or any amount of E. coli in upper digestive tract content is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A certain proportion of the patients with SCI show constipation in spite of the coexisting SIBO. Cheng et al reported that in patients with both SCI and SIBO, 22% showed constipation [ 22 ]. We believe that the, factors leading to constipation in our patient were stronger than those leading to diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…A known example is small intestinal bacterial overgrowth (SIBO), a malabsorption syndrome, which is referred to as an increase in the number of bacteria in the proximal part of small bowel or dysbiosis manifested as the presence of bacteria characteristic for colon. Cheng et al 85 showed the DVT as a dangerous complication associated with SIBO during posttraumatic hospitalization in patients after spinal cord injury. SIBO syndrome leads to increased bowel permeability with enhanced adsorption of LPS and other bacterial products.…”
Section: Gut Microbiome and Cardiovascular Diseasesmentioning
confidence: 99%